236U, 237Np and 239,240Pu as complementary fingerprints of radioactiveeffluents in the western Mediterranean Sea and in the Canada Basin (Arctic Ocean) - López-Lora, Mercedes; Chamizo, Elena; Levy, Isabelle; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655; Kenna, Timothy C. (Science of The Total Environment, 2021)
ISSN:0048-9697 ISSN:1879-1026